Universities, knowledge exchange and policy: A comparative study of Ireland and the UK. (4th August 2016) - Zhang, Qiantao; Larkin, Charles; Lucey, Brian M.
Abstract: This paper aims to provide one of the first cross-country empirical analyses of the intensity and diversity of knowledge exchange activities by academics. Focusing on the wide perspective of knowledge exchange, the results are based on two large-scale surveys with academics in the UK and Ireland and compare them in terms of: modes of interactions, types of partners, motivations and impacts of interactions, constraints on interactions and mission of higher education perceived by academics. It is found that academics in both countries are involved in a wide range of activities, with intellectual property activities being the interactions that they are least frequently engaged in. However, academics working at Irish and UK universities show distinct patterns of interactions with private sector companies and public sector organisations. Our analysis calls for caution over one country seeking to borrow policies from another without understanding the specific context of the higher education sector.